PENGARUH KOMPETENSI, BUDAYA KERJA DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI (STUDI KASUS PADA SALAH SATU KANTOR PEMERINTAHAN DI KABUPATEN BANDUNG BARAT) - Dani Hendrawan; Dedi Hadian; Senen Machmud (STMIK Mardira Indonesia, Bandung, 2020)
The state civil apparatus is an essential component in government organizations. This component greatly determines the level of success of the implementation of government functions in achieving its goals. For this reason, it is necessary to study employee performance, which is suspected to be influenced by competence, work culture, and work facilities at one of the regional government offices in West Bandung Regency. This study uses a quantitative approach by using primary data in conducting data analysis. A total of 71 respondents participated in this study. It is using path analysis techniques in analyzing data. The results showed that competence, work culture, and work facilities had a significant effect both partially and simultaneously. The research implication contributes to the development of competence, work culture, and work facilities by providing training in the use of technology and complying with the rules that apply to the organization. Keywords: Competence, Work Culture, Work Facilities, Employee Performance.